Tourism, mobility and second homes between elite landscape and common ground - Hall C Michael; Muller Dieter K (New Delhi Viva Books, 2006)
This volume describes the economic social & environmental impacts of second homes (cottage summer house & bach etc.) as well as their planning implications and places such discussions within the context of contemporary human mobility. It represents essent
Keywords: Tourism